Myths and Activism in Nawal El Saadawi's Memoar: A Daughter Of Isis (1999) - Rahayu, Harsiti Helen Padang; , Dr. M. Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2017)
The major problem of this study Myths and Activism in Nawal El Saadawi's Memoar: A Daughter of Isis (1999). The research uses qualitative research. Material Object is the book with the entitled A Daughter of Isis. The formal object of this study, research involves there is main issues Myth and Activism in Nawal El Saadawi's Memoirs. The result to the study shows there are six values derived from the Myth of A Daughter of Isis, namely: matrilineal system, women as superordinate, women as authority of magical power, model of motherly qualities, representation of reviving qualities of nature, nepresentation creative qualities. There are the values of the myths a closely related to Nawal El Saadawi activism. Matrilineal system is reflected in Nawal El Saadawi focus in extension in women. Increasing in quality: education, skill of creation, skill of organization, healthy, preventive in subordination and marginalization pass through postponement child marriage which to impact in Women Mortality. Nawal El Saadawi employed the form ideas of myth to deal with its real problem of the Egyptian society. Keywords: myths, activism, A Daughter of Isis, Nawal El Saadawi's,